Oxygen-enriched Air Decreases Ventilation during High-intensity Fin-swimming Underwater - Möller, Fabian; Jacobi, Elena; Hoffmann, Uwe; Muth, Thomas; Schipke, Jochen D. (International Journal of Sports Medicine, 2021)
Oxygen-enriched air is commonly used in the sport of SCUBA-diving and might affect ventilation and heart rate, but little work exists for applied diving settings. We hypothesized that ventilation is decreased especially during strenuous underwater fin-swimming when using oxygen-enriched air as breathing gas. Ten physically-fit divers (age: 25±4; 5 females; 67±113 open-water dives) performed incremental underwater fin-swimming until exhaustion at 4 m water depth with either normal air or oxygen-enriched air (40% O2) in a double-blind, randomized within-subject design. Heart rate and ventilation were measured throughout the dive and maximum whole blood lactate samples were determined post-exercise. ANOVAs showed a significant effect for the factor breathing gas (F(1, 9)=7.52; P=0.023; η2p=0.455), with a lower ventilation for oxygen-enriched air during fin-swimming velocities of 0.6 m·s−1 (P=0.032) and 0.8 m·s−1 (P=0.037). Heart rate, lactate, and time to exhaustion showed no significant differences. These findings indicate decreased ventilation by an elevated oxygen fraction in the breathing gas when fin-swimming in shallow-water submersion with high velocity (>0.5 m·s−1). Applications are within involuntary underwater exercise or rescue scenarios for all dives with limited gas supply.
Keywords: SCUBA diving; nitrox; underwater exercise; hyperoxia